Dysplasia Surveillance in Inflammatory Bowel Disease: A Cohort Study - Saraiva,Sofia (2021)
Abstract: Introduction: Patients with colonic inflammatory bowel disease (IBD) are at an increased risk for colorectal cancer (CRC), whereby surveillance colonoscopy is recommended. Aim: To study the clinical and endoscopic variables associated with dysplasia in IBD patients. Methods: A cohort study was conducted on IBD patients who were part of a colonoscopy surveillance program between 2011 and 2016. Results: A total of 342 colonoscopies were performed on 162 patients (105 with ulcerative colitis [UC] and 57 with Crohn’s disease). Random biopsies were performed at least once on 81.5% of patients; 33.3% of the patients underwent chromoendoscopy (CE) at least once. Endoscopically resectable lesions were detected in 55 patients (34%), and visible lesions deemed unfit for endoscopic resection were found in 5 patients (3.1%). Overall, 62 dysplastic visible lesions (58 with lowgrade dysplasia and 3 with high-grade dysplasia) and 1 adenocarcinoma were found in 34 patients. Dysplasia in random biopsies was present in 3 patients, the yield of random biopsies for dysplasia being 1.85%/patient (3/162), 1.75%/ colonoscopy (6/342), and 0.25%/biopsy (9/3,637). Dysplasia detected in random biopsies was significantly associated with a personal history of visible dysplasia (p = 0.006). Upon univariate analysis, dysplasia was significantly associated with the type of IBD, the performance of random biopsies, and CE (p = 0.016/0.009/0.05, respectively). On multivariate analysis, dysplasia was associated with duration of disease. Conclusion: Our data confirm that patients with long-standing IBD, in particular UC, should be enrolled in dysplasia surveillance programs, and that performing CE and random biopsies seems to help in the detection of colonic neoplastic lesions.